2021
DOI: 10.1177/15347354211058404
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Breast Cancer After Primary Treatment: A Matched Comparison Study of Disease-Free Survival in Women Who Do and Do Not Receive Adjunctive Naturopathic Oncology Care

Abstract: Purpose: To compare disease free survival experienced by women who received usual oncologic care compared to a cohort of women who received naturopathic oncology care in addition to usual care. Methods: Women with breast cancer who received naturopathic oncology (NO) care in Western Washington State (WA) (N = 176) were recruited to a prospective study of clinical health-related quality of life outcomes and then matched to women who received usual care (UC) only (N = 334). Results: Among 510 women with breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Between 2009 and 2015 a match-controlled longitudinal outcomes study of 750 women with breast cancer was conducted, and later published. 7 Then, in 2015 two naturopathic medical colleges, the Canadian College of Naturopathic Medicine and Bastyr University, partnered to develop a naturopathic oncology clinical research site consortium consisting of 12 North American clinics that provide cutting edge naturopathic oncology, typically adjuvant to standard conventional therapies to treat patients with advanced cancer. The Canadian /U.S.…”
Section: Collaborative Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Between 2009 and 2015 a match-controlled longitudinal outcomes study of 750 women with breast cancer was conducted, and later published. 7 Then, in 2015 two naturopathic medical colleges, the Canadian College of Naturopathic Medicine and Bastyr University, partnered to develop a naturopathic oncology clinical research site consortium consisting of 12 North American clinics that provide cutting edge naturopathic oncology, typically adjuvant to standard conventional therapies to treat patients with advanced cancer. The Canadian /U.S.…”
Section: Collaborative Researchmentioning
confidence: 99%
“…Between 2009 and 2015 a match-controlled longitudinal outcomes study of 750 women with breast cancer was conducted, and later published. 7 …”
Section: Accomplishmentsmentioning
confidence: 99%
“…To the editor: In a recent editorial, 1 Block discussed our finding that women who received naturopathic oncology care in addition to usual care experienced higher rates of recurrence compared to women in the usual care cohort. 2 What explains these surprising results?…”
mentioning
confidence: 99%
“…A recently published collaborative study, organized by Bastyr University and Fred Hutchinson Cancer Treatment Center, examined whether naturopathic care given adjunctively to conventional cancer treatment improves diseasefree survival in breast cancer patients. 1 This careful study, part of a series of articles, [2][3][4][5][6][7][8] concluded that patients who chose naturopathic oncology (NO) had worse disease-free survival than a comparable cohort of patients who received usual conventional cancer care (UC) without consulting naturopaths. The authors are to be congratulated for their thorough work, and for straightforwardly publishing a negative result that raises significant questions for integrative oncology as a whole, and particularly for complex integrative systems like naturopathy that routinely incorporate multiple lifestyle and herbal or supplemental interventions.…”
mentioning
confidence: 99%
“…In this matched cohort study, 1 patients with stages 0-III breast cancer in western Washington State, USA, were recruited. A total of 176 women who were receiving care for their cancer at any of 5 local naturopathic clinics were matched with women who were using UC.…”
mentioning
confidence: 99%